Experimental Study on the Mechanical Damage and Permeability Evolution of Coal With Different Moisture Contents Under Supercritical Carbon Dioxide Conditions - Xiaoqiang Zhang; Kai Wang; Yulong Jiang; Yuedong Liu; Pengqi Qiu; Shiyu Zhang; Tingting Cai; Jian Hou (Energy Science & Engineering)
ABSTRACT Using a self‐developed supercritical carbon dioxide (CO2) soaking system, the damage mechanisms and cracking characteristics of coal due to supercritical CO2 under the coupling of high‐temperature, high‐pressure, water, and the seepage evolution law and failure mode of coal bodies were revealed. On the basis of the acoustic emission response characteristics and physical experiments, a damage evolution model for the coal body was established. The results show that (1) the damage caused by supercritical CO2 to the coal body has a time effect and nonuniform characteristics. The compressive strength of the coal body from 0 to 3 days (d) decreases sharply as the supercritical CO2 soaking time increases. Additionally, the damaging effect of water and supercritical CO2 on the coal body is stronger than that of either factor alone (water or supercritical CO2). After 3 d of combined action of the two, the decrease in compressive strength accounts for 82.09% of the total decrease. (2) Under the action of supercritical CO2, the failure modes of coal remarkably differ, which are mainly manifested by the gradual evolution from tensile–shear failure to shear failure, with the instability form changing from sudden instability to quasi‐sudden instability. (3) At the same pore pressure, the coal permeability gradually increases from 0.3232 × 10−3 to 9.1422 × 10−3 md under the action of supercritical CO2. With the same soaking time, the permeability decreases as the effective stress increases. (4) On the basis of damage theory, a damage model for coal under supercritical CO2 soaking for different times was constructed. The model quantitatively reflects the influence of supercritical CO2 on coal damage under increased soaking time. The results of this research can provide technical guidance for CO2 geological sequestration in deep coal seams.